Chroma 422 subsampling for Bayer pattern in H.264 video coding. Issue 8 (1st April 2016) - Lin, T.‐L.; Liaw, P.‐S.; Chen, S.‐L.; Hsia, C.‐H.; Lin, S.‐Y.
Abstract : The optimal strategy of chroma 422 subsampling for Bayer pattern in H.264 video coding is proposed. The state‐of‐the‐art work uses a predetermined conversion method from colour filter array to YCbCr 422. Derived from this structure, first, 64 subsampling methods are designed to exploit more possibilities. Secondly, among which, the four optimal methods are found by the pre‐screening process, which show their better performances than the state‐of‐the‐art method by up to 2.57 dB in CPSNR averaged for different videos, demonstrating the practicability of the proposed methods. Finally, for the experiment consisting of the whole conversion and H.264 video encoding/decoding procedures, the proposed optimal methods perform better than the state‐of‐the‐art method under all different operating bitrates and different tested videos, by up to 2.25 dB in BDPSNR.